2002
DOI: 10.1016/s0006-3495(02)75239-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Environment on the Protein Dynamical Transition: A Neutron Scattering Study

Abstract: We performed an elastic neutron scattering investigation of the molecular dynamics of lysozyme solvated in glycerol, at different water contents h (grams of water/grams of lysozyme). The marked non-Gaussian behavior of the elastic intensity was studied in a wide experimental momentum transfer range, as a function of the temperature. The internal dynamics is well described in terms of the double-well jump model. At low temperature, the protein total mean square displacements exhibit an almost linear harmonic tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
188
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(205 citation statements)
references
References 40 publications
14
188
3
Order By: Relevance
“…According to Roh et al [3], the values of T D at h = 0.30 and 0.45 are both around 200 K, which is substantially different from the results of T X shown in this study. Moreover, Paciaroni et al [2] report that T D even decreases as h increases. To account for these results, we conclude that the PDT is not directly or solely induced by the dynamic crossover in the protein hydration water.…”
Section: -3mentioning
confidence: 98%
See 1 more Smart Citation
“…According to Roh et al [3], the values of T D at h = 0.30 and 0.45 are both around 200 K, which is substantially different from the results of T X shown in this study. Moreover, Paciaroni et al [2] report that T D even decreases as h increases. To account for these results, we conclude that the PDT is not directly or solely induced by the dynamic crossover in the protein hydration water.…”
Section: -3mentioning
confidence: 98%
“…Experimental studies show that the protein hydration water plays a key role in many aspects of protein behavior, which include the mean square displacement of the protein constituent atoms [2][3][4], the subpicosecond collective vibrations [5][6][7][8], the intraprotein α and β fluctuations [9,10], and the protein enzymatic activity [11]. Thus the study of the protein hydration water is crucial for the understanding of protein dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…We have not found such data. Some information comes from a neutron-scattering study on lysozyme embedded in pure glycerol (36) that showed that ͗x 2 (T) c ͘ for the glycerol and for the embedded lysozyme are identical. This result implies that the hydrogen atoms in the protein see the full motions of molecules in the shell and also suggests that glycerol can replace water.…”
Section: The ␤-Relaxation In Proteinsmentioning
confidence: 99%
“…The term 'slaving' has been used to express that water can impose its dynamical fingerprint on a protein 11,12 . Cryo-temperature dependent neutron scattering experiments revealed the solvent dependence of dynamical transitions in soluble proteins [13][14][15][16][17][18][19][20][21] and in RNA 22 and provided insights into the coupling between them. Molecular dynamics simulations suggested the onset of water translational diffusion to be at the origin of the dynamical transition 23,24 .…”
Section: Introductionmentioning
confidence: 99%